Interactive Learning Daily Muslim Prayer Application for Children on Android at DTA Ghoniyyul Hikmah - Hernawati; Iezam Kamalul Basyar; Sugeng Supriyadi; Suharjanto Utomo (FKOM UNIKU, 2025)
Learning daily prayers is important for Muslim children. The learning process in DTA Ghonniyul Hikmah generally uses the talqin method. To make memorizing prayers easier and more engaging, interactive learning media is needed. This research developed a daily prayer application for Muslim children based on Android. The application was designed using UML and implemented with Canva, PowerPoint, Audacity, and Android Studio. The features in the daily prayer application include images, Arabic and Latin script, translations, and prayer audio. The size of the application after being built is 48 MB. The questionnaire results show a positive response from users. As many as 86.9% of users agreed that the application is easy to use, and 78.2% felt helped in memorizing prayers. Overall satisfaction reached 78.3%. The majority of respondents were satisfied with the appearance and features of the application, and felt helped in memorizing prayers. Researchers suggest for future development that this daily prayer application have additional features such as animated videos and add even more daily prayers